Analisis Usahatani Jelai (Coix lacryma jobi-L) Studi Kasus Di Desa Loh Sumber Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - Nugroho, Agung Enggal; Damayanti, Arista (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2016)
The purpose of this study was to determine (1) revenue and income (profit) received by the farmers of the barley crop farming; (2) The number of R / C Ratio of selling barley crop production; (3) the obstacles or problems in cultivation of barley. Implementation research is from June to October 2016.The results showed that the total cost incurred in cultivating barley in the Loh Sumber Village in the harvesting period with an area of 1.5 ha is Rp. 9.02 million. With total revenue Rp. 10.92 million, in order to know the benefits of farmers is Rp. 1.90 million.Then the number of R / C Ratio on barley crop cultivation in the Loh Sumber Village in the harvest period is 1.21 so it can be concluded that the business is feasible to be developed in terms of quantity. But compared with the length of time the investment and the ability of optimal productivity, farming is still need to be improved so that the results can be maximized. Further research is also known to some obstacles encountered in the cultivation of barley in the Loh Sumber Village which are not yet certified seeds, pesticides are not yet available, and extreme weather are less supportive of the cultivation process.Keywords : Farming, Crop, Barley